2016
DOI: 10.1002/acr.22670
|View full text |Cite
|
Sign up to set email alerts
|

Toward Standardized Musculoskeletal Ultrasound in Pediatric Rheumatology: Normal Age‐Related Ultrasound Findings

Abstract: Objective. The Outcome Measures in Rheumatology Ultrasound Task Force has recently started to work on the validation and standardization of musculoskeletal ultrasound (MSUS) examination in children in order to improve its applicability to joint examination. Methods. This was a prospective multicenter study performed by 4 experts in pediatric MSUS, who independently collected representative images using predefined scanning procedures of 4 joints (knee, ankle, wrist, and second metacarpophalangeal joint) in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 19 publications
1
76
0
9
Order By: Relevance
“…Definitions for the US appearance of synovitis in children were successfully developed through a consensus process and validated on still images. This development represents another important step for a more reliable use of US in children, following the definition of findings of the normal joint and the publication of standard views to assess various joints . At the same time, these definitions clearly should be validated further in a patient‐based practical exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Definitions for the US appearance of synovitis in children were successfully developed through a consensus process and validated on still images. This development represents another important step for a more reliable use of US in children, following the definition of findings of the normal joint and the publication of standard views to assess various joints . At the same time, these definitions clearly should be validated further in a patient‐based practical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Following the agreement on definitions, all the participants were then invited to submit B‐mode and Doppler images of synovitis of the following joints: metacarpophalangeal (MCP), the wrist, and tibiotalar joints. Separate images were submitted for the following 4 age groups: toddler and preschool (ages 2–4 years), young children (ages 5–8 years), preadolescent (ages 9–12 years), and teenagers (ages 13–16 years) . Participants were asked to acquire the scans using standardized views, including longitudinal midline scans and a dorsal approach for MCP and wrist, as agreed in a previous exercise .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14] Studies on US of joints in healthy children and in JIA have already been published. [15][16][17][18][19][20][21] It has been suggested that US may be more sensitive in detecting joint inflammation in patients with JIA than the clinical evaluation. [22][23][24][25][26][27] However, the role of US-detected synovitis when clinical manifestations in JIA are absent is unknown.…”
Section: Introductionmentioning
confidence: 99%